Taxifolin alleviate metabolic and neurochemical alterations in the hippocampus and cortex of rats with rotenone-induced toxicity: In vivo and in silico insight - Courage Dele Famusiwa; Sunday Solomon Josiah; Ibrahim Olabayode Saliu; Toluwase Hezekiah Fatoki; Haruna Isiyaku Umar; Afolabi Clement Akinmoladun (Pharmacological Research - Modern Chinese Medicine, 2024)
Introduction: Exposure to rotenone could directly affects the function of mitochondrial which leads to neurodegeneration. This study evaluated the therapeutic potential of taxifolin (Huāqí sōng dài; 花旗松甙) to alleviate metabolic and neurochemical alterations in the hippocampal and cortical region of brain of rotenone-toxified rats. Methods: Male Wistar rats were subcutaneously administered 1.5 mg/kg rotenone for 10 days, followed by post-treatment with varying doses of taxifolin (0.25, 0.5 and 1.0 mg/kg) for 3 days through the same route. Activities of mitochondrial complex I, membrane ion pump and lactate dehydrogenase (LDH) were evaluated in the hippocampus and cortex of the brain of rotenone-toxified rats. Markers of neurotransmitter metabolism and oxidative stress were also biochemically estimated and molecular interaction between taxifolin and tyrosine hydroxylase, monoamine oxidase, glutamine synthetase and Na+/K+ATPase was determined by in silico simulation. Results: Taxifolin attenuated dysfunction of mitochondrial, Na+/K+ATPase, LDH and modulate neurotransmitter metabolism. Also, the elicited oxidative stress was mitigated by taxifolin in the hippocampus and cortex of the brain of rotenone-toxified rats. Furthermore, taxifolin showed excellent interactions with targeted enzymes in silico. The highest binding affinity was recorded in taxifolin-tyrosine hydroxylase complex. Hydrogen bond and hydrophobic interactions were the two key molecular interaction between the taxifolin and targeted enzymes. Discussion: Taxifolin alleviates metabolic and neurochemical aberrations in rotenone-induced neurotoxicity model in rats in vivo and exhibits promising interactions with specific target enzymes that are key to neurotransmission in silico.